Development of Electronic Worksheets with Environmental Approach in Structure and Function Plant Tissues Material to Train Crictical Thinking of Gtade 2nd High School Students - Dhea Maulidina Rohma; Rinie Pratiwi Puspitawati (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2021)
The Student worksheet is one of the teaching materials that are useful for supporting learning activities in the form of observation, research, and experiments aimed at solving problems that are related to living things and the environment. This research is development research using the ADDIE method (Analysis, Design, Development, Implementation, and Evaluation). The product developed is an electronic Student Activity Sheet. The purpose of this study was to develop electronic student worksheet teaching materials, describe the validity of electronic student worksheets, and test their practicality using student and teacher response questionnaires. The validity of the electronic student worksheet is reviewed from the results of the validation which were assessed by the material expert lecturers and education experts. Practicality is viewed from the response of the teacher as a practitioner and 11 students of 2nd-grade at Al Azhar senior high school Menganti Gresik. Data analysis techniques were carried out using quantitative description methods. The results of the study show that the electronic student worksheet is declared valid with a score percentage of 96.6% in the very valid category. an electronic student worksheet is also stated to be very practical given the teacher's response of 100% and students of 98.5%. thus electronic student worksheet with an environmental approach to the material structure and function of plant tissue to train students' critical thinking is declared valid and practical for teaching and learning activities. Keywords: Electronic worksheet, Stucture and function of plant tissue, Enviromental approach, Critical Thinking.